Visions about the Future of Banking - Hans J. Blommestein (SUERF - The European Money and Finance Forum, 2006)
I will address in this study the future of banking. This will be done against the backdrop of revolutionary forces shaping an increasingly fast-moving banking landscape. The first part of the study focuses on the ultra-long drivers of banking structures and institutions. To that end, I will identify the long-term determinants of our rapidly changing society. The second part will outline the implications of this long-term vision for the strategic direction and business models of banks in the near future.
Keywords: G2; G21; G22; G34; L2; O14; 330; banking; technology waves; fast-forward modernisation; post-utopian society; global techno-market order; life-cycle risks and products; new banking architectures and business models; Mergers and Acquisitions; risk diversification; Bank; Bankgeschäft; Branchenentwicklung; Geschäftsmodell